Aquaculture systems for wastewater treatment : an engineering assessment - Reed, Sherwood C.; Bastian, Robert K.; United States. Army Cold Regions Research Engineering Laboratory.; United States. Environmental Protection Agency. Office of Water Program Operations. Municipal Construction Division. (Washington, D.C. : Environmental Protection Agency, Office of Water Program Operations, Municipal Construction Division, 1981)
"MCD-68"--Cover. "EPA 430/9-80-007". "June 1980". Project cosponsored by EPA and U.S. Army Corps of Engineers Cold Regions Research and Engineering Laboratory. Includes bibliographies. Mode of access: Internet.